Implementasi Kebijakan Penyelenggaraan Lalu Lintas Dan Angkutan Jalan (Studi Kasus Penyediaan Perlengkapan Jalan Umum yang Berstatus Sebagai Jalan Kota di Kecamatan Pekanbaru Kota) - Ikhsan Risniawan Putra; Febri Yuliani; Hasim As'ari (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2022)
Abstract This research is based on the purpose of Regional Regulation No.10 of 2017 which is to realize road traffic and transportation in Pekanbaru Kota can be safe, comfortable and efficient which has not been reached. the purpose of this research is to determine the implementation and what factors hinder implementation the policy the provision of road equipment in Pekanbaru Kota Distric. This research uses Grindle theory, namely the content variables of this policy include: group interests, types of benefits, changes to be achieved, location of decision making, program implementation, resources used. The policy environment includes: Power, interests, and strategy of policy actors; Characteristics of the institutions; Group compliance level. This study used descriptive qualitative method. The results of this study indicate that the implementation or application of the road equipment provision policy in Pekanbaru Kota District is seen from the process or workflow is good, but there are several obstacles, namely: road facilities that are less maintenance so that the benefits of this policy have not been maximally realized. The factors that hindered this policy were limited budget, bad behavior of public elements and poor maintenance of road equipment. Keywords : Implementation of Policy, Traffic, Road Equipment.